Mechanical peeling of van der Waals heterostructures: Theory and simulations. (July 2019) - Lin, Kui; Zhao, Ya-Pu
Abstract: Mechanical peeling is crucial for the assembly process of van der Waals (vdW) heterostructures. We provide a new theory to describe the peeling of vdW heterostructures based on interatomic potential. Representatively, we present the peeling of graphene on molybdenum disulfide (MoS2 ) using a bottom-up approach. The results show that there are three stages (the initial, stable and jump out of contact stages) in the entire peeling process. We find that the traditional continuum model is only suitable for the stable stage, while our theory can describe the entire process from (the initial unstable) contact to the end of the stable stage. In addition, we discovered a new characteristic length, the elasto-peeling length L ep = 2 D ∕ Δ γ = 4 σ 0 2 π D ∕ H, that is a crucial parameter that reflects the bending ( D ) and interfacial properties ( Δ γ ) of the layered materials during peeling. Finally, the theory as expressed by the Hamaker constant ( H ) is presented. Our findings may help to reveal the underlying mechanisms in the peeling of layered materials at the atomic scale.